2013
DOI: 10.1002/anie.201209116
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Visible‐Light‐Driven Water Oxidation by Iron Complexes at pH 7–9: Evidence for Dual‐Active Intermediates in Iron‐Catalyzed Water Oxidation

Abstract: Ironing out a solution: Chemical and visible‐light‐driven water oxidation by iron complexes and iron salts at pH 7–9 has been investigated. The iron complexes and salts act as precatalysts (see scheme) to produce α‐Fe2O3 nanoparticles that are the real catalyst for the water oxidation with a turnover number over 1000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
124
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(126 citation statements)
references
References 34 publications
2
124
0
Order By: Relevance
“…10 Lau and coworkers have suggested that at low pH multidentate N-donor iron complexes accomplish water oxidation through a molecular iron-oxo intermediate. 11 At high pH, however, they claim that ligand dissociation occurs to generate Fe 2 O 3 nanoparticles that catalyze water oxidation.…”
mentioning
confidence: 99%
“…10 Lau and coworkers have suggested that at low pH multidentate N-donor iron complexes accomplish water oxidation through a molecular iron-oxo intermediate. 11 At high pH, however, they claim that ligand dissociation occurs to generate Fe 2 O 3 nanoparticles that catalyze water oxidation.…”
mentioning
confidence: 99%
“…It is usually applied to monitor the formation of metal oxide/hydroxide or other insoluble particles in reaction solutions [23][24][25].…”
Section: Page 5 Of 48mentioning
confidence: 99%
“…22a-d) with oxidant [Ru(bpy) 3 ](ClO 4 )3 in borate buffer at pH 8.5[25]. It was found that, all of the complexes except Fe(mcp)Cl 2 (20b-2Cl) showed the activity in chemical water oxidation[30].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Although, there has been significant progress in designing molecular catalysts for H 2 evolution, the search for highly active catalysts that can operate in aqueous solution still remains a challenge. In general, iron(III) complexes are employed as electrocatalysts for water oxidation [26][27][28][29][30], but there are few reports on water reduction by iron(III) complexes [31]. Herein, we present the synthesis and characterization of an iron complex, [LFeCl] 1, as well as its catalytic properties.…”
Section: Introductionmentioning
confidence: 99%